2022
DOI: 10.3390/biom12081101
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Identifying the Transition Zone in Long-Segment Hirschsprung Disease: Investigating the Muscle Unit to Ganglion Ratio

Abstract: Hirschsprung disease (HSCR) is characterised by the absence of enteric ganglia along variable lengths of the distal bowel. Current gold standard treatment involves the surgical resection of the defective, aganglionic bowel. Clear and reliable distinction of the normoganglionated bowel from the transition zone is key for successful resection of the entire defective bowel, and the avoidance of subsequent postoperative complications. However, the intraoperative nature of the tissue analysis and the variability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…It could indicate that signals that direct these axons to their targets are deficient. As in the human disease, there were increased numbers of goblet cells and an increase in EEC numbers in the mucosa of the aganglionic region, but, overall, tissue histology was normal as has been previously observed in humans ( Thiagarajah et al, 2014 ; Kapur, 2016 ; Yang et al, 2022 ). Thus, the Ednrb −/− Hirschsprung disease model in rat appears to be representative of Hirschsprung disease in general.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It could indicate that signals that direct these axons to their targets are deficient. As in the human disease, there were increased numbers of goblet cells and an increase in EEC numbers in the mucosa of the aganglionic region, but, overall, tissue histology was normal as has been previously observed in humans ( Thiagarajah et al, 2014 ; Kapur, 2016 ; Yang et al, 2022 ). Thus, the Ednrb −/− Hirschsprung disease model in rat appears to be representative of Hirschsprung disease in general.…”
Section: Discussionsupporting
confidence: 72%
“…Histological investigation showed that the cellular components of all tissue layers were normal. This parallels the situation in humans, where it is difficult to recognize differences between ganglionic and aganglionic regions, or between healthy colons and colons from Hirschsprung patients, except by close examination of the ganglia and the innervation of the colon ( Kapur, 2016 ; Yang et al, 2022 ). We found that the thickness of the external muscle was similar for the ganglionic and aganglionic regions, but the distal region failed to grow in diameter and a considerable size mismatch was apparent by 12 weeks after surgery.…”
Section: Discussionmentioning
confidence: 68%
“…Congenital long-segment Hirschsprung's disease involves a broad range of segments, with stenotic segments extending from the anus to the descending colon or even the transverse colon. There is currently debate in clinical practice regarding the treatment of long-segment Hirschsprung's disease, mainly focusing on whether to stage the surgical procedures and the choice of the de nitive surgical method [4][5]. Concerning staged surgeries, literature suggests that for cases with recurrent small bowel colitis unresponsive to conservative treatments, severe malnutrition, signi cant dilation and thickening of the proximal colon making the identi cation of the lesion and transition segment challenging, presence of intestinal perforation (mainly in the ileocecal region), and some cases with extensive lesions (from the upper-middle descending colon to the proximal end of the splenic exure), a diverting stoma can be created initially [6][7].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been found that the size of the muscle unit/neuron ratio can be used to determine the transition zone of long-segment congenital megacolon, which can better determine the area of surgical resection. The type and content of mucosal nerve fibers and the size of the intestinal ganglion in the intraoperatively resected intestine can also be used as predictors to determine the probability of enterocolitis after HSCR ( 18 , 90 ).…”
Section: Intestinal Neuroimmune Modulation In the Diagnosis And Treat...mentioning
confidence: 99%